2009
DOI: 10.1016/j.intell.2008.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Imaging intelligence with proton magnetic resonance spectroscopy

Abstract: Proton magnetic resonance spectroscopy ( 1 H-MRS) is a technique for the assay of brain neurochemistry in vivo. N-acetylaspartate (NAA), the most prominent metabolite visible within the 1 H-MRS spectrum, is found primarily within neurons. The current study was designed to further elucidate NAA-cognition relationships, particularly whether such relationships are moderated by sex, or tissue type (gray or white matter). We administered standard measures of intelligence to 63 young, healthy subjects and obtained s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 48 publications
0
20
0
6
Order By: Relevance
“…Second, the relationship between g and NAA is better explained by regional than global indices. This is especially possible in the light of earlier finding by Jung et al (Jung et al, 2009), who showed in the same individuals both negative and positive correlations between IQ and NAA depending of the region examined. It would then follow that these differences could cancel each other out at the global level.…”
Section: Discussionmentioning
confidence: 60%
“…Second, the relationship between g and NAA is better explained by regional than global indices. This is especially possible in the light of earlier finding by Jung et al (Jung et al, 2009), who showed in the same individuals both negative and positive correlations between IQ and NAA depending of the region examined. It would then follow that these differences could cancel each other out at the global level.…”
Section: Discussionmentioning
confidence: 60%
“…Importantly, this “disinhibition” likely corresponds to both BVSR aspect of creative cognition, although the bias would be toward elaboration , where multiple ideas can be generated in an environment lacking refinement, formal testing, or selection pressures. Our research tends to support the notion that some normal brains, performing better on standard creativity measures, are more “disinhibited” in their organization, with certain regions having lower cortical volume (Jung et al, 2010c), lower white matter fidelity (Jung et al, 2010a), and (at or below a verbal IQ of 116) anterior cingulate biochemistry tending to “gate” frontal information flow (Jung et al, 2009a). Certain clinical entities (particularly semantic dementia) and lesions within isolated anterior frontal and inferior parietal brain regions support the notion of disinhibitory facilitation of blind variation serving creative cognition (Miller et al, 1998; Shamay-Tsoory et al, 2011; Abraham et al, 2012a).…”
Section: What Does It All Mean?mentioning
confidence: 56%
“…Recent studies with larger sample sizes have reported associations between intelligence and white matter tract structure (from diffusion imaging [48,49] ) as well as white matter integrity (volume of white matter hyperintensities, number of microbleeds, number of iron deposits) [50] ; a combination of these with brain volume and cortical thickness has been shown to account for as much as 20% of the variance in g [51] . The role of white matter is further corroborated by several MR spectroscopy studies which find a relationship between N-acetyl aspartate, a metabolite of the oligodendrocytes that constitute the myelin sheath [52] , and IQ scores. Neuroimaging studies remain correlative in nature, and causal inference is limited.…”
Section: Structural Studiesmentioning
confidence: 73%